Organizational Effectiveness: Bibliometric Analysis - Shahib Ansari; Theresia Martina; Munawara Salfitri; Hanny; Rofina Ernesta (SMARTINDO, 2023)
Purpose - This study aims to identify and analyze trends in the publication of articles on the Journal of Organizational Effectiveness Design/methodology/approach - The research design uses the Bibliometric analysis method. Data collection was obtained from the Google Scholar database because it is the largest database with the period category during the 2016-2022 period. In data mapping, researchers use vosviewer with article categories and organizational effectiveness keywords Findings and Discussion – The results of the VosViewer analysis show that there are 25 items related to organizational effectiveness with 7 research clusters, 162 links and 820 link strengths. Research on organizational effectiveness is closely related, among others, to performance, organizational goals, organizational culture